Chińska polityka surowcowa w Afryce - Konieczny, Dominik (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The first Chinese-African Co-operation Forum took place in Beijing in 2000. It established a mechanism for promoting diplomatic relations, trade and investment between China and African countries. China's fast developing economy has an impact on growing demand for raw materials, mainly for oil and energy. That is the reason why one of the principal interests of the PRCh in the continent is an access to natural resources. China invested a lot in extractives industries. Sudan, where China is the most important investor in oil exploration, production, transportation and infrastructure is the example of how China comes to Africa with what analysts call "Soft power strategy" or "complete package strategy", which includes technical expertises, money, scholarships, and teams of doctors. China also became very active in West coast of Africa, Nigeria and Angola. Of course, China's economic interests in Africa are much wider. China telecoms and constructions companies win a lot of contracts and intensely co-operate with African governments. On the other hand, African continent represents a large market for cheap Chinese made goods, so this is the reason why Chinese products flooding African market. It should be pointed out that some of goods are complementary to African ones, but many hard compete in continent, so many nations are suffering from growing import from China, for example, export of Chinese textiles to Africa is undermining local African industry while the growth of Chinese export to the United States is shutting down the promising growth of African export in this field. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 240-251